The Existence of Local Culture-Based Education in the Formation of Student Character - Firman; Chana Indika (Konsultan Jurnal Ilmiah Indonesia, 2025)
Local culture-based education is an approach that integrates local wisdom values into the learning process. This article discusses the concept, implementation and role of local culture-based education in student character building. Through a literature review, it is found that local culture-based education does not only include teaching arts or customs, but also includes value systems, social norms and traditional wisdom. Its implementation requires the active role of teachers as facilitators, students as learning subjects, and the community as supporters. The development strategy can be done through integrating cultural elements in learning materials, using traditional games, and creating a conducive learning environment. The results show that local culture-based education makes a significant contribution in shaping student character rooted in noble cultural values, as well as being a bulwark in facing the challenges of globalization.